Analisis Kualitas Air PAM Layak Minum dengan Metode Random Forest dan Decision Tree - Stefani Kelin Martha Ampak; Anak Agung Istri Ngurah Eka Karyawati; I Komang Arya Ganda Wiguna (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Water is an important source of life for living things including humans. Human needs for water include water that is suitable for use in cooking, washing, and bathing activities that are clean and healthy, as well as water that is safe to drink. Drinking Water Companies (PAM) have a vital role in providing water that meets the standards of consumption eligibility. This study aims to analyze the quality of PAM water by utilizing the Random Forest method as a classification method. The data used include physical, chemical, and microbiological parameters of water. The use of the random forest method was chosen because of its ability to handle complex data and produce accurate predictions. The results of the study showed that the random forest model was able to classify water quality with a high level of accuracy and identify the parameters that most influence the eligibility of drinking water. This study is expected to help related parties in monitoring and improving the quality of PAM water so that it is in accordance with the established health standards.